Pengaruh Pemberian Teh Hijau (Camellia sinensis) terhadap Gambaran Histopatologi Paru-Paru Tikus Putih (Rattus novergicus) Jantan Galur Sprague Dawley yang di Papar Uap Rokok Elektronik - Ni Putu Sari Widiyani; susianti; Putu Ristyaning Ayu Sangging (Medula, 2022)
E-cigarettes are easy to obtain and feel safer than conventional cigarettes, making smokers begin to change their habits in using conventional cigarettes. This trend has made e-cigarettes increasingly popular. Toxic contained in e-cigarettes causes an oxidative stress process that triggers an inflammatory response and causes respiratory problems. Green tea extract is believed to be an antioxidant to suppress the oxidative stress process. The study used a pure experimental design using 30 white rats of the Sprague Dawley strain. There was a change in histopathological damage in all samples where there was a significant difference in the control group, but not significant in the value of the vape control (K2) with treatment group 1 (50 mg/kgBW) p=0.163. E-cigarette consumption leads to an increase in circulating markers of oxidative stress. E-cigarette vapor induces an increase in cellular reactive oxygen species which in turn increases circulating inflammatory markers. Green tea polyphenols seek reactive oxygen species (ROS) by generating more stable phenolic radicals. The protective effect is attributed to the antioxidant capacity thereby reducing lung tissue damage. The conclusion is that there is an effect of giving green tea extract at a dose of 50 mg/kgBW but there is an effect of giving green tea extract at a dose of 100 mg/kgBW and 200 mg/kgBW on changes in the histopathological picture of the lungs of white rats (Ratus novergicus) Sprague dawley strain exposed to steam. electronic cigarette.